Enhanced cell survival of pH-sensitive bioenergetic nucleotide nanoparticles in energy/oxygen-depleted cells and their intranasal delivery for reduced brain infarction. (1st September 2016) - Choi, Yeon Su; Cho, Dong Youl; Lee, Hye-Kyung; Cho, Jung-Kyo; Lee, Don Haeng; Bae, You Han; Lee, Ja-Kyeong; Kang, Han Chang
Graphical abstract: Abstract: Nucleotides (NTs) (e.g., adenosine triphosphate) are very important molecules in the body. They generate bioenergy through phosphate group release, are involved in various biological processes, and are used to treat various diseases that involve energy depletion. However, their highly anionic characteristics might limit delivery of exogenous NTs into the cell, which is required to realize their functions as bioenergy sources. In this study, ionic complexation between Ca 2+ and NT phosphates was used to form Ca 2+ /NT nanocomplexes (NCs), and branched polyethyleneimine (bPEI1.8kDa ) was coated on the surface of Ca 2+ /NT NCs via a simple electrostatic coating. The resultant Ca 2+ /NT/bPEI1.8kDa NCs were approximately 10–25 nm in size and had positive zeta-potentials, and their NT loading efficiency and content were approximately 60–75% and 10–20 wt%, respectively. Faster NT release from Ca 2+ /NT/bPEI1.8kDa NCs was induced by lower pH and by NTs with fewer phosphates. Reductions in cell viability in response to low temperature, serum deprivation, or hypoxia were recovered by NT delivery in Ca 2+ /NT/bPEI1.8kDa NCs. In a middle cerebral artery occlusion (MCAO)-induced post-ischemic rat model, the BBB (blood brain barrier)-detoured intranasal administration of Ca 2+ /ATP/bPEI1.8kDa NCs induced a better reduction in infarct volume and neurological deficits than did free ATP. In conclusion, intracellular NT delivery using Ca 2+ /NT/bPEI1.8kDa NCs might potentially enhance cell survival and reduce infarction in energy-/oxygen-depleted environments. Statement of Significance: This study describes bioenergetic nucleotide delivery systems and their preparation, physicochemical characterization, and biological characterization both in vitro and in vivo. Nucleotides, such as adenosine triphosphate (ATP) and guanosine triphosphate (GTP), are very important signaling and energy molecules in the body. However, research on these nucleotides using nanosized carriers has been very limited. Liposomal ATP delivery has been reported in heart and renal ischemia studies. Notably, although this delivery system has potential in energy-depleted environments (e.g., low temperature, serum deprivation, and hypoxia) and in brain ischemia, studies are lacking regarding these systems. Thus, we designed polycation-shielded Ca 2+ /nucleotide nanocomplexes using simple mixing, which produced 10- to 25-nm-sized particles. The nanocomplexes released nucleotides in response to acidic pH, and they enhanced cell survival rates under conditions of low temperature, serum deprivation, or hypoxia. Importantly, the nanocomplexes reduced cerebral infarct volumes in a post-ischemic rat model. Thus, our study demonstrates that a novel nucleotide nanocomplex could have potential for preventing or treating diseases that involve energy depletion, such as cardiac, cerebral, and retinal ischemia, and liver failure.